A study on skewness and kurtosis estimators of wind speed distribution under indeterminacy - Aslam, Muhammad (Theoretical and applied climatology, 2021)
In the present paper, two important measures of skewness and kurtosis under indeterminacy are presented. The basic measures to evaluate the nature of the wind speed in the presence of neutrosophic numbers are given. The importance of the proposed measures of skewness and kurtosis under neutrosophic statistics is discussed over the existing measures of skewness and kurtosis under classical statistics. From the wind speed analysis, it is concluded that the wind speed data have heavy-tailed distribution. Therefore, it is recommended to apply a heavy-tailed distribution, like Cauchy distribution, for forecasting and estimation of energy produced by wind speed.